Obstetric violence as perceived by nursing students - Kamila Machado Correa; Josemar Batista; Suellen da Rocha Lage Moraes (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To identify the perception of Nursing students about the understanding, causes, and prevention actions of obstetric violence. Method: A descriptive, exploratory, and qualitative study carried out at a private university center in Paraná. The data was collected from June to July 2022, using a semi-structured questionnaire for 10 Nursing students and submitted to thematic content analysis. Results: The following category emerged: knowledge of Nursing students about obstetric violence, made up of two subcategories: obstetric violence: concept, types, and understanding of the causes in the perception of Nursing students; and empowerment of women, active listening and training of health professionals to prevent practices that constitute obstetric violence. According to the interviewees, obstetric violence is characterized by abuse and mistreatment by health professionals, in its physical, verbal, moral, psychological, and sexual forms. Professional and structural issues were identified as the main causes, while professional training and women's empowerment were identified as factors for preventing the problem. Final considerations: The students understood the practices characterized as obstetric violence, were familiar with their main causes, and pointed to professional training and the need to provide women with preventive actions against this type of violence in obstetric services.